Anne of the island - Montgomery, L. M. (Lucy Maud), 1874-1942.; Graham, Mark, 1952- (New York : L. C. Page & Company, Inc., 1915)
Continues the adventures of Anne Shirley and her friends at college.
Keywords: Orphans -- Fiction; Self-perception -- Fiction; Interpersonal relations -- Fiction; Universities and colleges -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Nova Scotia -- History -- 20th century -- Fiction; Canada -- History -- 1914-1945 -- Fiction